Carbon storage and sequestration in Southeast Asian urban clusters under future land cover change scenarios (2015–2050) - Kamarajugedda, Shankar Acharya; Johnson, Justin Andrew; McDonald, Robert; Hamel, Perrine (Frontiers in Environmental Science, 2023)
Land-use land-cover (LULC) changes are occurring rapidly in Southeast Asia (SEA), generally associated with population growth, economic development and competing demands for land. Land cover change is one of the vital factors affecting carbon dynamics and emissions. SEA is an important region to study urban-caused LULC emissions and the potential for nature based solutions (NBS) and nature climate solutions (NCS), as it is home to nearly 15% of the world’s tropical forests and has some of the world’s fastest rates of urban growth. We present a fine-scale urban cluster level assessment for SEA of current (2015) and future (2050) scenarios for carbon sequestration service and climate mitigation potential. We identified 956 urban clusters distributed across 11 countries of SEA. Considering the urban expansion projected and decline in forests, this region could see a carbon loss of up to 0.11 Gigatonnes (SSP4-RCP 3.4 scenario). Comparing carbon change values to urban emissions, we found that offset values ranged from -34 % to +4 %, with the average offset value ranging from -2 % (Scenario SSP1 RCP2.6) to -21%. We also found that a few medium and large urban clusters could more than double existing carbon emissions in 2050 in the SSP3 and SSP4 RCP 3.4 scenarios, while a minority of clusters could offset their emissions under SSP1. Our study confirms that NCS, and particularly reforestation, are in many cases able to offset the direct emissions from land cover conversion from SEA urban clusters. Hence, documenting the plausible LULC transitions and the associated impacts gains significance in SEA region as the results can be useful for informing policy and sustainable land management.